The Effects of Additives to Lightweight Aggregate on the Mechanical Properties of Structural Lightweight Aggregate Concrete - Khoshvatan, Mehdi; Pauraminia, Majid (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper, the effects of different percentages of additives (perlite, LECA, pumice) on the mechanical properties of structural lightweight aggregate concrete were tested and evaluated. For the research, 14 mixing designs with different amounts of aggregate, water, and cement were made. Experimental results showed that the specific gravity of lightweight structural concrete made from a mixture of LECA, pumice, and perlite aggregates could be 25-30% lighter than conventional concrete.
Keywords: lightweight concrete; perlite; lightweight aggregate; pumice; leca; mechanical properties; beton lekki; perlit; kruszywo lekkie; pumeks; keramzyt; właściwości mechaniczne